Clinical Implications of Primary Cilia in Skin Cancer - Abrar Choudhury; Neil M. Neumann; David R. Raleigh; Ursula E. Lang (Adis, Springer Healthcare, 2020)
Abstract The primary cilium is a cell surface organelle that is an important component of cellular biology. While it was once believed to be a vestigial structure without biologic function, it is now known to have essential roles in critical cellular signaling pathways such as Hedgehog (HH) and Wnt. The HH and Wnt pathways are involved in pathogenesis of basal cell carcinoma and melanoma, respectively, and this knowledge is now beginning to inform therapeutic and diagnostic options for patients. The purpose of this review is to familiarize clinicians with primary cilia biology and how this complex cellular organelle has started to translate into clinical care.